Heterogeneity of treatment dropout: PTSD, depression, and alcohol use disorder reductions in PTSD and AUD/SUD treatment noncompleters. (13th December 2018) - Szafranski, Derek D.; Gros, Daniel F.; Acierno, Ron; Brady, Kathleen T.; Killeen, Therese K.; Back, Sudie E.
Abstract: Treatment dropout is often assumed to be due to worsening or lack of symptom improvement, despite minimal research examining symptom change among treatment dropouts. Thus, the present study examined symptom change in veterans who discontinued evidence‐based treatment for comorbid posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD). Participants were veterans who completed at least one session of a 12‐session Concurrent Treatment of PTSD and Substance Use Disorders using Prolonged Exposure (COPE) for comorbid PTSD/AUD. The study analyses investigated the 43% of the sample ( n  = 22) that did not complete the full 12‐session protocol and were therefore considered treatment dropouts. Symptom changes in PTSD, AUD, and depression were examined among dropouts using two methods: (a) clinically significant change criteria and (b) good end‐state criteria. Results indicated that a significant proportion of treatment dropouts displayed clinically significant improvement and/or met good end‐state criteria for PTSD (40–59%), AUD (66%), and depression (45–68%) prior to dropping out. The results revealed that participants who displayed symptom improvement attended more treatment sessions and completed more imaginal exposures than participants who did not experience significant improvement. Together, the findings add to a growing body of literature suggesting that a large proportion of treatment dropouts may actually improve. Although preliminary, the findings challenge the notion that treatment dropout is always associated with negative outcomes.